Effect of soil and foliar applied potassium and nitrogen on yield of potato (Solanum tuberosum) in alluvial soils of Punjab, India - BRAR, M S; KAUR, NAVDEEP (The Indian Journal of Agricultural Sciences, 2011)
A study conducted for 3 years (2000-2002) on a coarse loamy, non-calcareous, Typic ustorthents showed little effect of nitrogen (urea) or foliar application of KN03 on potato (Solanum tuberosum L.) yield in the absence of potassium application. In presence of potassium, a significant increase in the tuber yield was obtained with increasing level of nitrogen and foliar application of KNOr Application of potassium increased the per cent distribution of bigger size tubers. Among the 2 foliar fertilizers, ie KCI (MOP) and KN03 , potassium nitrate resultd in the highest yield at concentration of2% which was superior to 1%. The yield of potato increased over the period of growth and over 90% yield was obtained at 75 days after sowing. ’Kufri Badshah’ gave significantly higher yield than ’ Kufri Jyoti’ mainly owing to higher yield of large-size tubers. Potassium and nitrogen uptake in tuber and straw increased significantly with soil and foliar application of K.